Situating Risk in Young People’s Social and Moral Relationships in Peru - Crivello, G; Boyden, J (2011)
In this paper we report on a long-term study of child poverty being carried out by Young Lives in Peru and examine how poverty mediates a multitude of other risks in children’s lives. We offer three main arguments in relation to children’s experiences of risk in our sample. The first is that risk is not simply a feature of ‘extraordinary’ childhoods and ‘extraordinary’ circumstances but also an integral part of everyday, ‘ordinary’ lives in which the young negotiate multiple, interacting challenges. The second concerns the importance for children of the social and moral dimensions of risk and how these shape their responses to adversity. The third makes the case that in situations of high levels of interdependence between generations children can play an essential part in household risk reduction. Our findings suggest that while current approaches to ‘risk’ tend to focus on individualised risks which are singled out according to so-called ‘objective’ criteria these often fail to account for children’s own priorities, perceptions and subjective experiences within the context of their daily lives.